Effects of Exercise Intensity on Postexercise Endothelial Function and Oxidative Stress. (25th October 2015) - McClean, Conor; Harris, Ryan A.; Brown, Malcolm; Brown, John C.; Davison, Gareth W.
Abstract : Purpose . To measure endothelial function and oxidative stress immediately, 90 minutes, and three hours after exercise of varying intensities. Methods . Sixteen apparently healthy men completed three exercise bouts of treadmill running for 30 minutes at 55%V ˙ O 2 m a x (mild); 20 minutes at 75%V ˙ O 2 m a x (moderate); or 5 minutes at 100%V ˙ O 2 m a x (maximal) in random order. Brachial artery flow-mediated dilation (FMD) was assessed with venous blood samples drawn for measurement of endothelin-1 (ET-1), lipid hydroperoxides (LOOHs), and lipid soluble antioxidants. Results . LOOH increased immediately following moderate exercise (P < 0.05 ). ET-1 was higher immediately after exercise and 3 hours after exercise in the mild trial compared to maximal one (P < 0.05 ). Transient decreases were detected forΔ F M D /S h e a r A U C from baseline following maximal exercise, but it normalised at 3 hours after exercise (P < 0.05 ). Shear rate was higher immediately after exercise in the maximal trial compared to mild exercise (P < 0.05 ). No changes in baseline diameter, peak diameter, absolute change in diameter, or FMD were observed following any of the exercise trials (P > 0.05 ). Conclusions . Acute exercise at different intensities elicits varied effects on oxidative stress, shear rate, and ET-1 that do not appear to mediate changes in endothelial function measured by FMD.